About dynamic method of flow structure control in vortex chamber - Турик, Владимир Николаевич; Бабенко, Виктор Витальевич; Милюков, Дмитрий Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2012)
The work is dedicated to choice of the way of heat and mass transfer control in vortex chambers according to different appointment. The version of dynamic method of flow structure control in vortex chamber by means of influence on powerful coherent vortex formation in chamber dead-end region is proposed. The knowledge lack about initiation and evolution of this discovered recently coherent vortical phenomenon caused organization of experimental research by a pneumometric method for determination of influence of the turbulent flooded stream, injecting through a dead-end nozzle, on current structure in dead-end part of cylindrical vortex chamber. The visualization data of flow structure were obtained by means of cameras and digital video camera. On the basis of the visualization pictures analysis and constructed speed fields the interaction features of the butt-end stream with the most power sated vortex formation defining the general structure of the current in dead-end and flowing (active) parts of the vortex chamber are shown. It is shown that conjunction by directions of the control streaming flow and the powerful coherent vortex gives steady oscillated circular rotation of the flow on inside wall along the chamber axis. Opposite direction of the dead-end control streaming flow leads to formation of quasi-tornado vortex pair on chamber wall. Results of the investigation are of great interest for designers of the vortex chambers in power, metallurgical, chemistry engineering, aircraft industry etc.